2022
DOI: 10.3390/life12101604
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Livestock Demography and Infrastructure in Driving Foot and Mouth Disease Dynamics

Abstract: Transboundary animal diseases, such as foot and mouth disease (FMD) pose a significant and ongoing threat to global food security. Such diseases can producearge, spatially complex outbreaks. Mathematical models are often used to understand the spatio-temporal dynamics and create response plans for possible disease introductions. Model assumptions regarding transmission behavior of premises and movement patterns ofivestock directly impact our understanding of the ecological drivers of outbreaks and how to best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…The duration that individual herds contribute to transmission will also be important for understanding how the composition of premises contributes to the overall outbreak dynamics. Studies have shown that aspects of demography, including premises clustering, and the number of large farms in a given area, impact the outcome of potential FMD outbreaks (Werkman et al, 2016;Tsao et al, 2019;Gilbertson et al, 2022). Using well informed estimates for the duration of infectiousness for herds of different sizes will help disentangle the impact of herd size on duration of an outbreak within a herd versus the duration of an outbreak across multiple herds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration that individual herds contribute to transmission will also be important for understanding how the composition of premises contributes to the overall outbreak dynamics. Studies have shown that aspects of demography, including premises clustering, and the number of large farms in a given area, impact the outcome of potential FMD outbreaks (Werkman et al, 2016;Tsao et al, 2019;Gilbertson et al, 2022). Using well informed estimates for the duration of infectiousness for herds of different sizes will help disentangle the impact of herd size on duration of an outbreak within a herd versus the duration of an outbreak across multiple herds.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming the entire herd or flock is a single unit is a simplifying assumption but it provides policy makers with metrics of interest about potential outbreaks, including the number of potential herds or flocks infected and the spatial extent. However, some outbreak metrics of interest to policy makers are influenced by within-herd dynamics, particularly overall outbreak duration (Chis Ster et al, 2012;Gilbertson et al, 2022), which is important for understanding potential economic impacts and can be underestimated by models that do not include within-herd dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Building on these, the USAMM model [25], which has been applied and modified extensively [76][77][78][79][80][81][82][83][84], uses a Bayesian kernel approach to reconstruct the US cattle trade network. Similarly to GMs, movement probabilities were modelled as a function of the number of cattle premises at the origin and destination, and the distance between them, while also incorporating data on historical state-level cattle inflows.…”
Section: Other Statistical Models (N = 6)mentioning
confidence: 99%
“…Airborne transmission also remains possible, depending on the distance to neighboring barns and other farms. The annual probability of an FMD outbreak in a given facility (H), was modeled using an empirical distribution fitted to the data on predicted incidence of FMD outbreaks from five models [23][24][25][26][27]. More details about the estimates used are available in S1 Appendix.…”
Section: Plos Onementioning
confidence: 99%